Outcome of preimplantation genetic diagnosis using FISH analysis for recurrent miscarriage in low-risk reciprocal translocation carriers. (August 2016) - Pundir, Jyotsna; Magdalani, Laurice; El-Toukhy, Tarek
Abstract: Objective: To assess PGD outcome using FISH analysis in couples with a history of recurrent miscarriage associated with a parental carrier of reciprocal translocation. Study design: Couples in whom one partner was a carrier of a reciprocal translocation and had a history of two or more miscarriages and a low risk of a live born offspring with an unbalanced chromosomal rearrangement, underwent PGD treatment between 2000 and 2012. Results: 91 couples started 171 fresh and 11 frozen PGD cycles. Of the fresh cycles, 162 (95%) reached oocyte retrieval and 107 (63%) had embryo transfer. In 14 cycles (8%), surplus embryos were cryopreserved. Pregnancy was achieved in 52 fresh PGD cycles, leading to 20 miscarriages and 32 live births. Eleven frozen embryo transfer cycles resulted in two miscarriages and three live births. The overall live birth rate was 19% per fresh and frozen PGD cycle started (35/182) and miscarriage rate was 39% per pregnancy (22/57). The cumulative live birth rate was 32% per couple (29/91). Conclusion: After PGD for recurrent miscarriage in low-risk reciprocal translocation carriers, the miscarriage risk remains high and chance of live birth is low. For those translocation carriers, natural conception may be a better option.